Question
upstudy study bank question image url

\begin{tabular}{l}\( \begin{array}{l}a+b+c \\ \frac{a+b+c}{b+c}=-1\end{array} \) \\ Determine the \( 50^{\text {th }} \) term of the above pattern: \\ \hline\end{tabular}

Ask by Vaughan Coles. in South Africa
Feb 19,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The 50th term of the pattern is -100.

Solution

To solve the problem, we need to analyze the given equations and find a pattern that allows us to determine the \( 50^{\text{th}} \) term. 1. **Extract Known Conditions:** - We have two equations: 1. \( a + b + c \) 2. \( \frac{a + b + c}{b + c} = -1 \) 2. **Solve the Second Equation:** - From the second equation, we can rewrite it as: \[ a + b + c = - (b + c) \] - This simplifies to: \[ a + b + c = -b - c \] - Rearranging gives: \[ a + 2b + 2c = 0 \] - Thus, we can express \( a \) in terms of \( b \) and \( c \): \[ a = -2b - 2c \] 3. **Substituting Back:** - Now we can substitute \( a \) back into the first equation: \[ (-2b - 2c) + b + c = -b - c \] - Simplifying this gives: \[ -b - c = -b - c \] - This is always true, indicating that \( a, b, c \) can take on various values as long as they satisfy the relationship derived. 4. **Finding the Pattern:** - The equations suggest a linear relationship among \( a, b, c \). If we let \( b = n \) and \( c = m \), we can express \( a \) as: \[ a = -2n - 2m \] - The terms \( a, b, c \) can be represented in a sequence based on \( n \) and \( m \). 5. **Determining the \( 50^{\text{th}} \) Term:** - If we assume a simple pattern where \( a, b, c \) are integers, we can generate terms based on \( n \) and \( m \). - For example, if we let \( n \) and \( m \) increase sequentially, we can find the \( 50^{\text{th}} \) term by substituting \( n = 50 \) and \( m = 50 \) into our expressions. 6. **Calculating the \( 50^{\text{th}} \) Term:** - Let’s calculate: \[ a = -2(50) - 2(50) = -100 - 100 = -200 \] - Thus, the \( 50^{\text{th}} \) term can be represented as: \[ a + b + c = -200 + 50 + 50 = -100 \] Therefore, the \( 50^{\text{th}} \) term of the pattern is \(-100\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( \frac{a+b+c}{b+c}=-1 \), we start by manipulating the equation. 1. Multiply both sides by \( b+c \) (assuming \( b+c \neq 0 \)): \[ a+b+c = - (b+c) \] 2. This simplifies to: \[ a+b+c = -b - c \] 3. Rearranging gives us: \[ a + 2b + 2c = 0 \] Next, we can express \( c \) in terms of \( a \) and \( b \): \[ c = -\frac{a + 2b}{2} \] Next, let's substitute values into the expression of \( a + b + c \): \[ a + b + c = a + b - \frac{a + 2b}{2} \] \[ = a + b - \frac{a}{2} - b = \frac{a}{2} + b - b = \frac{a}{2} \] Thus, the first term is \( \frac{a}{2} \). Now we can observe that the sequence involves \( a, b, c \). If we assume a simple increment pattern, such as \( a_n = n, b_n = n+1, c_n = n+2 \), continuing like this will give terms like: 1. \( 1+2+3 = 6 \) 2. \( 2+3+4 = 9 \) 3. \( 3+4+5 = 12 \) This continues with a pattern \( 3, 6, 9, \ldots \) which is an arithmetic sequence with a difference of \( 3 \). To find the \( 50^{\text{th}} \) term: \[ T_n = 3n \] Thus, \[ T_{50} = 3 \times 50 = 150 \] The \( 50^{\text{th}} \) term of the pattern is therefore \( 150 \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy